2022
DOI: 10.3390/su14031285
|View full text |Cite
|
Sign up to set email alerts
|

How Digital Platforms Enhance Urban Resilience

Abstract: Throughout human history, natural and man-made disasters have devastated cities in unpredictable ways. Cities must therefore respond faster and better to minimize the risks posed by disasters. Nowadays, with the rapid development of communication technology, digital platforms are increasingly becoming an indispensable part of people’s lives; hence, they could become a new force for urban resilience. However, there are few studies on how digital platforms enhance urban resilience, so this paper attempts to use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In general, the module value range is [0, 1], the module value Q > 3 clusters considerably, the average profile value S > 0.5 clusters fairly, and the average profile value S > 0.7 clusters precisely. The mapping information column clearly showed that the module value Q and mean profile value S values were within a suitable range; thus, their use as a basis for analysis was reliable [29].…”
Section: Methodsmentioning
confidence: 91%
“…In general, the module value range is [0, 1], the module value Q > 3 clusters considerably, the average profile value S > 0.5 clusters fairly, and the average profile value S > 0.7 clusters precisely. The mapping information column clearly showed that the module value Q and mean profile value S values were within a suitable range; thus, their use as a basis for analysis was reliable [29].…”
Section: Methodsmentioning
confidence: 91%
“…Resilience building in different regions has a profound impact on regional development, most directly by improving regional resilience [ 18 ], indirectly by improving urban air quality, conserving resources [ 19 ], protecting ecosystems [ 20 ], promoting urban transformation [ 21 23 ], and promoting circular economy [ 24 ]. With the improvement of people’s education and health [ 25 ] and digital platforms [ 26 ], urban resilience will also increase.…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are various digital platforms in practice, such as social media, mobile operating systems and peer-to-peer platforms (Qiu et al , 2022). Similarly, a dedicated digital platform can be established for collaboration and coordination between the government and the citizens.…”
Section: Research Backgroundmentioning
confidence: 99%